1994
DOI: 10.1080/10292389409380492
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal variation in the late quaternary vegetational history of Northwest Greece

Abstract: The palaeoecological sites of Gramousti lake and Rezina marsh, northwest Greece, although only 20 kin apart are at contrasting altitudes of 285 m a.s.1. and 1800 m a.s.1. Altitudinal difference between the two sites is shown to have a significant effect upon the postglacial vegetational history of the region. Rezina marsh is the highest and smallest site to be studied thus far in Greece and provides some of the first evidence for the location of cold-stage temperate tree refugia. Migration of tree populations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…Some of the lowland areas would have been allocated to crop-growing; if clearance for creating pasture land was not practised, or only on a small scale, for most of the Greek Neolithic, as suggested by the dominance of woodland in pollen diagrams (e.g. Willis 1994a) and if animals browsed in the woods, as was practised for example in Switzerland (Ackeret et al 1999: 180) and still is in parts of modern Greece, then browsing/grazing of the forested landscape might have required movement away from the settlement. Pollen diagrams from upland sites in northern Greece show a reduction in diversity and density of most tree taxa, as well as an increase in Hornbeam pollen (a species that flourishes in cleared and grazed woodland), suggesting possible human interference with natural woodland vegetation, due to pastoral activity, at around 5000 BC (Willis 1994b: 105-6).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the lowland areas would have been allocated to crop-growing; if clearance for creating pasture land was not practised, or only on a small scale, for most of the Greek Neolithic, as suggested by the dominance of woodland in pollen diagrams (e.g. Willis 1994a) and if animals browsed in the woods, as was practised for example in Switzerland (Ackeret et al 1999: 180) and still is in parts of modern Greece, then browsing/grazing of the forested landscape might have required movement away from the settlement. Pollen diagrams from upland sites in northern Greece show a reduction in diversity and density of most tree taxa, as well as an increase in Hornbeam pollen (a species that flourishes in cleared and grazed woodland), suggesting possible human interference with natural woodland vegetation, due to pastoral activity, at around 5000 BC (Willis 1994b: 105-6).…”
Section: Discussionmentioning
confidence: 99%
“…Although the microenvironment created by the coniferous trees is demonstrated in this record, other areas that might have provided such oases include southfacing slopes, high-altitude sites, and areas of well-drained soils. Previous researchers suggested that small pockets of microenvironmentally favorable conditions played an a important refugial role in the survival of temperate tree taxa in southern Europe during the last full-glacial (Bennett et al, 1991;Willis, 1992;Tzedakis, 1993;Willis, 1994b). However, until now there has been little evidence to support this suggestion.…”
Section: Fig 3 Chronological Position Of Macroscopic Charcoal Samplmentioning
confidence: 98%
“…Unfortunately, none of these nearby sequences have an independent, absolute chronology for these marine deposits. In fact, the Lake Bufi age model was obtained by the tuning main vegetation changes with the pollen sequence of Lake Gramousti (Pindus Mountains, NW Greece) (Willis, 1992) assumed to be synchronous. According to this correlation, marine deposits in Lake Bufi were deposited prior to ca.…”
Section: The Transition From Open Marine To Lagoon Conditions (2420-1mentioning
confidence: 99%